Optimum feature size of randomly textured glass substrates for maximum scattering inside thin-film silicon solar cells - Sahraei, Nasim; Venkataraj, Selvaraj; Aberle, Armin G.; Peters, Marius (Proceedings of SPIE - The International Society for Optical Engineering, 2014)
Optimization of light scattering by designing proper randomly textured surfaces is one of the important issues when designing thin-film silicon solar cell structures. The wavelength region that needs to be scattered depends on the absorber material and the thickness of the solar cell. The optimum morphology of the textured substrate can be defined regarding the wavelength range intended for scattering. Good scattering is experimentally achieved by optimizing the fabrication process of the randomly textured substrate. However, optimum morphological parameters have not been analytically formulated. In this work we develop the morphological criteria for optimum light scattering in a-Si:H solar cells using Aluminum Induced Texture (AIT) glass superstrates. Transmission haze is widely used as an evaluating factor for scattering properties. Haze can be easily measured for the substrate/air interface. However, the relevant scattering properties are those in the absorber material. These properties cannot be measured directly, but can be predicted by an appropriate model. The simple model for haze calculation based on scalar scattering theory cannot correctly estimate the haze value because it only considers the root mean square (RMS) roughness of the textured surface, which does not contain information about lateral feature size. In addition, the opening angel of the haze measurement is not considered in the equation. In this work, we demonstrate that the power spectral density (PSD) function of the randomly textured surface can provide the missing information in the haze equation. A general formulation for calculating the lateral feature size based on the PSD function is presented. We use this calculated haze value based on PSD to find the optimum lateral feature size for scattering a specific wavelength into the desired material. The optimum lateral feature size for scattering 620-nm light, which is weakly absorbed in a-Si:H, is shown to be 100 nm. © 2014 SPIE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Aluminium induced textured glass (ait); Correlation length; Haze; Light scattering; Optics at surfaces; Power spectral density; Roughness; Thin-film solar cells